AN ASSESSMENT OF MGNREGP PROGRESS IN SANGLI DISTRICT OF MAHARASHTRA (International Journal of Food and Nutritional Sciences, 2022)
Sangli district is the part of south-western Maharashtra. It is one of the developing districts and agricultureis backbone of the district economy. The rural mass of the district is heavily depends on the agriculture andallied activities for their livelihood sources. The majority of the district area is frequently suffers from thedrought conditions. The eastern part of the district is often facing the issue of water scarcity and watershortage for both agriculture and domestic uses purpose. The significant industrial development of thedistrict is only observed in western and central part of the district. The MGNREGP is the anti povertyweapon which provides 100 days guaranteed employment to the unskilled rural workforce. In factMGNREGP is main livelihood source of the rural people in the drought hit area of the Sangli district.Through the MGNREGP, there are several works completed in the district and in progress. The communitydevelopment works, traditional water bodies renovation work, social forestry, farm roads, farm ponds,rural connectivity, and environmental resources conservation works are either completed or being inprogress since last decade. Under this backdrop, the present research study has examined the progress ofMGNREGP in Sangli district based on block level secondary data. The study has covered the three yearperiod. The physical and financial progress of the MGNREGP has assessed and attempts are made toexamine the trends therein. The study is analytical in nature and it has arrived at conclusion thatMGNREGP has significantly grown up in the district during the period under consideration and it hasproviding employment to rural unskilled workforce. It is also revealed from the study that the out of total21.08 lakh rural population of the Sangli district, 5.44 lakh people (i.e 25.80 percent) are engaged inMGNREGP. However, at present the active numbers of workers are seen only 0.67 lakh. The proportion ofSC workers is also seen significant in total MGNREGP workforce. Thus programme is not only playingsignificant role in rural development of Sangli district but in upliftment of the weaker segment of thesociety.